SWI/SNF-type complexes–transcription factor interplay: a key regulatory interaction - Anna Maassen; Jaroslaw Steciuk; Magdalena Wilga; Jakub Szurmak; Damian Garbicz; Elzbieta Sarnowska; Tomasz J. Sarnowski (Cellular & Molecular Biology Letters)
Abstract ATP-dependent switch/sucrose nonfermenting-type chromatin remodeling complexes (SWI/SNF CRCs) are multiprotein machineries altering chromatin structure, thus controlling the accessibility of genomic DNA to various regulatory proteins including transcription factors (TFs). SWI/SNF CRCs are highly evolutionarily conserved among eukaryotes. There are three main subtypes of SWI/SNF CRCs: canonical (cBAF), polybromo (pBAF), and noncanonical (ncBAF) in humans and their functional Arabidopsis counterparts SYD-associated SWI/SNF (SAS), MINU-associated SWI/SNF (MAS), and BRAHMA (BRM)-associated SWI/SNF (BAS). Here, we highlight the importance of interplay between SWI/SNF CRCs and TFs in human and Arabidopsis and summarize recent advances demonstrating their role in controlling important regulatory processes. We discuss possible mechanisms involved in TFs and SWI/SNF CRCs-dependent transcriptional control of gene expression. We indicate that Arabidopsis may serve as a valuable model for the identification of evolutionarily conserved SWI/SNF–TF interactions and postulate that further exploration of the TFs and SWI/SNF CRCs-interplay, especially in the context of the role of particular SWI/SNF CRC subtypes, TF type, as well as cell/tissue and conditions, among others, will help address important questions related to the specificity of SWI/SNF–TF interactions and the sequence of events occurring on their target genes. Graphical Abstract